Rock Star : The Making of Musical Icons from Elvis to Springsteen - Shumway, David R. (Book collections on Project MUSE., 2014)
"Shumway investigates the rock star as a particular kind of cultural construction, different from mere celebrity. After the golden age of moviemaking, media exposure allowed rock stars more political sway than Hollywood's studio stars, and rock stars gradually replaced movie stars as key cultural heroes. Because of changes in American society and the media industries, rock stars have become much more explicitly political figures than were the stars of Hollywood's studio era. Rock stars, moreover, are icons of change, though not always progressive, whose public personas read like texts produced collaboratively by the performers themselves, their managers, and record companies. These stars thrive in a variety of media, including recorded music, concert performance, dress, staging, cover art, films, television, video, print, and others."--Publisher's information